Job Demands-Control-Social Support Model and coping strategies: predicting burnout and wellbeing in a group of Italian Nurses / Il modello Domanda-Controllo-Sostegno Sociale e il ruolo delle strategie di coping nella predizione del benessere e del ... - Pisanti, Renato (La Medicina del Lavoro, 2012)
SummaryBackground: Nursing is generally considered to be a stressful profession. Objectives: The purpose of the present study was to test the core hypotheses of the job demands-control-social support model (JDCS) of Karasek & Theorell (1990). In order to refine and extend the JDCS model, we also analyzed the direct and interactive role of three coping strategies: task- oriented, emotion-oriented, and avoidance-oriented coping. Methods: Questionnaire data from 1383 nurses (77% female) were collected. Results: Controlling for demographic variables and non-linearity of the associations between job characteristics and outcomes (job satisfaction, burnout dimensions, psychological distress, and somatic complaints), hierarchical regression analyses indicated that job control and social support combined additively (p